Hydrodynamic Investigation and Analysis for Rod Deep Pumping Wells in the Established Regimes - Qasimova, S.A. (Herald of Azerbaijan Engineering Academy, 2024)
By analyzing the hydrodynamics of wells at the established modes, it was found that the flow rate of oil, water and gas of a well depend on the parameters of a deep pumping unit, bottom well pressure, and values of depression the flow rate of the well. Studies have shown that the fluid supply mode of a deep pumping well can be changed over a wide range, without stopping the operation of the well, by changing the length of the movement, it is possible to switch to four or five different regimes of operation. The pump with the smallest diameter should be lowered into the well and the number of oscillations of the rocking machine should be minimized using depth remote manometers. According to the results, indicator diagrams are built in two ways, while it is possible to determine the depth of the dynamic level of the liquid using an echo sounder.